Evaluation of the effectiveness of the use of free diced cartilage in dorsal and tip nasal rhinoplasty - Amr Gouda Shafik; Mohamed Naguib Mohamed; Hassan Mohamed Hassan (The Egyptian Journal of Otolaryngology, 2020)
Abstract Background Rhinoplasty is considered one of the most challenging operations in the plastic surgery. Esthetic or functional reshaping purposes of the nose can be stressing for both surgeon and patient. Different types of graft materials have been used to perform augmentation rhinoplasty. Free diced cartilage (FDC) was recently established in dorsal nasal rhinoplasty for better handling of irregularities as well as contour deficits of dorsal nasal outcomes. The main purpose of the present study is to assess the effectiveness of the use of FDC in dorsal nasal and nasal tip rhinoplasty and evaluation of its advantages and disadvantages using the validated Nasal Obstruction Symptom Evaluation (NOSE) scale and the Rhinoplasty Outcome Evaluation (ROE) questionnaire to assess nasal obstruction and patient satisfaction. Results This prospective study was conducted between March 2018 and December 2019, 20 patients were included and planned for rhinoplasty using FDC to camouflage dorsal and nasal tip deformities. All patients (11males and 9 females) underwent open rhinoplasty through inverted v columellar incision, taken FDC from nasal septum. A statistical significant difference between pre- and post-operative NOSE scores was found (P < 0.001). Post-operative rhinoplasty outcome evaluation scores ranged from 45 to 100 with mean ± SD (83.15 ± 13.22). Excellent satisfaction was the most noted in 17 patients (85%), while 2 patients (10%) reported good satisfaction and 1 patient (5%) with acceptable satisfaction. Conclusion It was found that the FDC technique is an effective method for camouflage and augmentation of nasal dorsum as well as nasal tip in reconstructive and esthetic rhinosurgery for either primary or secondary rhinoplasty.